An evaluation of life cycle assessment and its application to the closed-loop recycling of carbon fibre reinforced polymers. (1st March 2020) - Tapper, Rhys J.; Longana, Marco L.; Norton, Andrew; Potter, Kevin D.; Hamerton, Ian
Abstract: Life cycle assessment (LCA) is a valuable tool for establishing the environmental burdens of a composite material over its lifetime. It is therefore of importance to the composites industry as a material selection tool when determining the applicability of recycled composites in the component design phase. This review paper evaluates the LCA framework and its ability to accurately determine the benefits of closed-loop composite recycling, with the aim of aiding future material selection for recycled CFRP. LCA is a powerful tool for CFRP assessment when used in combination with an economic and technical component as covered by the integrated Life Cycle Engineering approach. The broad range of values available in LCA databases may prove an issue for cross comparison between studies and provide disparate results leading to impractical conclusions. The use phase offers the greatest potential for CFRP emissions savings in the transport sector; the advent of closed-loop recycling for CFRP may provide the multiple use phases required to breakeven on the significant energy burden of production or possibly provide net environmental savings gains over traditional materials.